Out of the blue : September 11 and the novel - Versluys, Kristiaan (Columbia University Press, 2009)
Writers have represented 9/11 and its aftermath with varying degrees of success. In Out of the Blue, Kristiaan Versluys focuses on novels that move beyond patriotic clichés and cheap sensationalism and provide new insights into the emotional and ethical impact of these traumatic events & mdash;and what it means to depict them. Versluys focuses on Don DeLillo's Falling Man, Art Spiegelman's In the Shadow of No Towers, Jonathan Safran Foer's Extremely Loud and Incredibly Close, Frédéric Beigbeder's Windows on the World, and John Updike's Terrori.